The Social Construction of Trust - Weber, Linda R. author. aut Link
X, 180 p.
Keywords: Based on in-depth interviews designed to determine what trust is, how it is built, and how it is destroyed, this important new resource provides extensive insight into the fundamental process of interpersonal trust in the day-to-day lives of average people. The Social Construction of Trust furnishes qualitative data analysis and offers a detailed definition of trust in a sociological context. Discussing the theoretical and methodological foundation of the work, The Social Construction of Trust -Examines the stages of the interactional construction of trust orientation; -Investigates the form and content of trust violation; -Analyzes forgiveness based on reconciliation through trust reconstruction; -Presents a perspective on the relationship between trust and self; -Delineates the practice of trust in interpersonal relationships; -And more. This unique text is a valuable reference for sociologists, social and clinical psychologists, and students in these disciplines.